UTILIZATION OF LAND IN THE RIVER BORDER AREA IN GROGOL SUB-DISTRICT SUKOHARJO DISTRICT IN 2018 - Munandar Cahya Santoso; Agus Sudargono; Talitha Rahmawati (Universitas Veteran Bangun Nusantara, 2020)
Utilization of land in the river border area in Grogol Sub-District, Sukoharjo District in 2018. The purpose of this research is to : (1) Knowing the Land Use of River Border Areas in Grogol sub-district; (2) Knowing the types and characteristics of buildings that dominate in the River Border Area, Grogol Sub-District in 2018; (3) Knowing the Suitability of River Border Area Land Use in Grogol Sub-District in 2018 with River Border Regulations. This research uses google earth remote sensing image interpretation method with Quickbird satellite imagery, which describes and knows land use, types and characteristics of buildings and the suitability of land use with boundary regulations. The data collection technique used is through interpretation of satellite imagery, direct field observation. The data analysis technique used was data reduction, data presentation, drawing conclusions / verification. The results of this study are : (1) Utilization of land in the river border area in Grogol Sub-District, Sukoharjo District in 2018, that is Bengawan Solo and Kali Samin rivers consisting of 5 land uses, that is Rice Fields, Garden, House, Empty land, and Factory. (2) The type of land use for house buildings with the characteristics of permanent buildings is more dominant. (3) Most of the land use is in accordance with the Regulation of the Minister of Public Works and Housing Number 28 / PRT / M / 2015, because the use of building land in the river border area in Grogol Sub-District is only about 25 percent or about 42 hectares of the 168 hectares of the river border area in Grogol Sub-District in 2018.